2019
DOI: 10.1016/j.electacta.2018.10.201
|View full text |Cite
|
Sign up to set email alerts
|

One-step wet-spinning process of CB/CNT/MnO2 nanotubes hybrid flexible fibres as electrodes for wearable supercapacitors

Abstract: Fibres made from different nanostructured carbons (carbon black (CB)), carbon nanotubes (CNT) and CB/ CNT were successfully developed by wet-spinning. The variation of dispersion conditions (carbon nanomaterial concentration, dispersant/Carbon nanomaterial concentration ratio, CB/CNT concentration ratio, pH) resulted in different electrochemical performance for each type of fibres. Fibres with the best capacitance values (10 F g −1) and good cycling stability (89%) were obtained from fibres containing 10% carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Similar conductivity values were measured for all fiber treatment times with no further improvement observed for longer times (either 60 or 120 min), suggesting that all modification of the fibers occurred within the first 5 min. Xia et al found that the conductivity increased after treatment with dilute sulfuric acid for up to three treatments [13]. For the solvents used here, the treatments were repeated with multiple immersions, showing no further increase after the first submersion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar conductivity values were measured for all fiber treatment times with no further improvement observed for longer times (either 60 or 120 min), suggesting that all modification of the fibers occurred within the first 5 min. Xia et al found that the conductivity increased after treatment with dilute sulfuric acid for up to three treatments [13]. For the solvents used here, the treatments were repeated with multiple immersions, showing no further increase after the first submersion.…”
Section: Resultsmentioning
confidence: 99%
“…This trend however was not observed with other PEDOT: PSS sources (as shown later in Figure 4). This is partially attributed to the removal of insulating PSS from the fiber, specifically from the fiber surface and the reordering of the polymer chains and is discussed later in the sections dealing with Raman spectroscopy and XPS [7,13,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This area emerged less than ten years ago 117 and keeps growing because of the interest in 'wearable Internet' and smart textiles 110 . Initially, carbon materials were used, but conductive polymers, metal oxides 118 and MXenes 119 recently entered the field. Storing the amount of energy required for powering devices, from LEDs to sensors and communication (antennas) on the limited surface of a garment (less than 1 m 2 ) is challenging, if only EDLC is used.…”
Section: Discussionmentioning
confidence: 99%
“…MnOx composite electrodes fabricated on flexible substrates are being examined for use as supercapacitors [63][64][65][66] We previously reported a single-material electrode of manganese oxide that resulted in a high level of specific capacitance [9]. That version's high specific capacitance was due to the morphology of the multi-plate thin film, which was fabricated via the thermal decomposition of manganese formate-amine ink at 260 o C.…”
Section: Introductionmentioning
confidence: 99%